Relative efficacy and safety of ticagelor vs clopidogrel as a function of time to invasive management in non–ST‐segment elevation acute coronary syndrome in the PLATO trial. Issue 6 (9th June 2017) - Pollack, Charles V.; Davoudi, Farideh; Diercks, Deborah B.; Becker, Richard C.; James, Stefan K.; Lim, Soo Teik; Schulte, Phillip J.; Spinar, Jindrich; Steg, Philippe Gabriel; Storey, Robert F.; Himmelmann, Anders; Wallentin, Lars; et al.
Abstract: Background: Guidelines suggest that "upstream" P2Y12 receptor antagonists should be considered in patients with non–ST‐segment elevation acute coronary syndromes (NSTE‐ACS). Hypothesis: Early use of ticagrelor in patients managed with an invasive strategy would be more effective than clopidogrel because of its more rapid onset of action and greater potency. Methods: In the PLATO trial, 6792 NSTE‐ACS patients were randomized to ticagrelor or clopidogrel (started prior to angiography) and underwent angiography within 72 hours of randomization. We compared efficacy and safety outcomes of ticagrelor vs clopidogrel as a function of "early" (<3h) vs "late" (≥3h) time to angiography. Adjusted Cox proportional hazards models evaluated interaction between randomized treatment and time from randomization to angiography on subsequent outcomes. Results: Overall, a benefit of ticagrelor vs clopidogrel for cardiovascular death/myocardial infarction/stroke was seen at day 7 (hazard ratio [HR]: 0.67, P = 0.002), day 30 (HR: 0.81, P = 0.042), and 1 year (HR: 0.80, P = 0.0045). There were no significant interactions in the <3h vs ≥3h groups at any timepoint. For major bleeding, overall there was no significant increase (HR: 1.04, 95% confidence interval: 0.85‐1.27); but there was a significant interaction with no difference between ticagrelor and clopidogrel in the early group (HR: 0.79), but higher bleeding risk with ticagrelor in the late angiography group, at 7 days (HR: 1.51, P int = 0.002). Patterns were similar at 30 days and 1 year. Conclusions: The benefit of ticagrelor over clopidogrel was consistent in those undergoing early and late angiography, supporting upstream use of ticagrelor.